End-to-end simulation of the C-ADS Injector Ⅱ with a 3-D field map - 王志军 何源 王旺生 刘淑会 贾欢 李超 徐显波 陈熙荫 (Chinese physics C, 2013)
The InjectorⅡ, one of the two parallel injectors of the high-current superconducting proton driver linac for the China Accelerator-Driven System （C-ADS） project, is being designed and constructed by the Institute of Modern Physics. At present, the design work for the injector is almost finished. End-to-end simulation has been carried out using the TRACK multiparticle simulation code to check the match between each acceleration section and the performance of the injector as a whole. Moreover, multiparticle simulations with all kinds of errors and misalignments have been performed to define the requirements of each device. The simulation results indicate that the lattice design is robust. In this paper, the results of end-to-end simulation and error simulation with a 3-D field map are presented.